2021
DOI: 10.1152/ajpendo.00126.2021
|View full text |Cite
|
Sign up to set email alerts
|

Central GLP-1 contributes to improved cognitive function and brain glucose uptake after duodenum-jejunum bypass on obese and diabetic rats

Abstract: The improvement of cognitive function following bariatric surgery has been highlighted, yet its underlying mechanisms remain elusive. Finding the improved brain glucose uptake of patients after Roux-en-Y gastric bypass (RYGB), duodenum-jejunum bypass (DJB) and sham surgery (Sham) were performed on obese and diabetic Wistar rats, and intracerebroventricular (ICV) injection of glucagon-like peptide-1 (GLP-1) analog liraglutide (Lira), antagonist exendin-(9-39) (Exe-9), and the viral-mediated GLP-1 receptor (Glp-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…The findings suggest that lipids reduce the release of enteric hormones, accelerating glucose transit (or vice versa), and that cryptal function may be regulated by glucose exposure, both in the duodenum and in the colon. Interestingly, the exclusion of GI walls from food transit (e.g., following bariatric surgery [ 13 , 15 ]) or the use of drugs reducing motility (e.g., GLP1 receptor agonists [ 15 , 16 , 31 ]) result in an elevation in adipose tissue [ 13 , 16 ] or brain [ 15 , 31 ] GU. In our study, the co-administration of glucose and lipids caused an intermediate situation, with fast transit and low incretin levels, likely balancing brain effects, while stimulating adipose tissue GU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings suggest that lipids reduce the release of enteric hormones, accelerating glucose transit (or vice versa), and that cryptal function may be regulated by glucose exposure, both in the duodenum and in the colon. Interestingly, the exclusion of GI walls from food transit (e.g., following bariatric surgery [ 13 , 15 ]) or the use of drugs reducing motility (e.g., GLP1 receptor agonists [ 15 , 16 , 31 ]) result in an elevation in adipose tissue [ 13 , 16 ] or brain [ 15 , 31 ] GU. In our study, the co-administration of glucose and lipids caused an intermediate situation, with fast transit and low incretin levels, likely balancing brain effects, while stimulating adipose tissue GU.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the administration of a single glucose or standard meal, passing through the GI tract, has been associated with systemic and liver inflammation [ 11 , 12 ], though it remains to be established whether these effects require specifically the GI entry route. Accumulating evidence from, e.g., bariatric surgery [ 13 , 14 , 15 ] or drugs affecting GI function (GLP1 agonists [ 15 , 16 ], metformin [ 17 , 18 , 19 , 20 ]), point to the GI tract as an important regulator of tissue glucose uptake (GU).…”
Section: Introductionmentioning
confidence: 99%
“…It is a great challenge of modern societies to devise efficient strategies to prevent and treat neurodegeneration in the elderly. LANCL1 and LANCL2 are both highly expressed in the central nervous system (CNS) [ 19 ], where the glucose transporters comprise GLUT1 and GLUT4 [ 50 , 51 ], both targets of LANCL1/2-mediated increased expression. A role for LANCL1/2 in protection from neuroinflammation, particularly from its oxidation-mediated damage, could be hypothesized from the fact that both proteins bind to reduced glutathione (GSH) and have an SH3-binding domain [ 52 ].…”
Section: Neuroprotective Effects Of the Aba/lancl Systemmentioning
confidence: 99%
“…In a recent study, we demonstrated the ability of 68 Ga-NODAGA-exendin-4 to visualize GLP-1 receptor expression on pancreatic beta cells [ 31 ]. Since GLP-1 receptor agonists are successfully used to reduce body weight and improve insulin resistance in obese subjects, and bariatric surgery may influence GLP-1 levels [ 32 ], we recently started a clinical study on the effects of bariatric surgery on GLP-1 binding as measured with 68 Ga-NODAGA-exendin-4 PET.…”
Section: Introductionmentioning
confidence: 99%